The Ability of Grade X Students of A Senior High School in Identifying and Writing Recounts in English - Sandhy Leksmana Ligito; Agnes Santi Widiati (Magister Scientiae, 2008)
This paper reports the result of a study aimed at finding out the ability of Senior High School students in identifying and writing recount texts. As such, the objectives of the study are to find out whether the students are able to identify a recount texts and its generic structure (orientation, event(s), and re-orientation) and to find out whether they are able to write a recount text with proper generic structure. Fourty three subjects were given questions concerning recount texts and asked to write a recount text. The result shows that most of the students were able to write a recount text with the proper generic structure showing all the elements of a recount text, but many of them had the difficulty in identifying a recount text and its generic structure.